THE USE OF ENGLISH COLLOCATIONS IN READER’S DIGEST - Yudita Putri Nurani Sinaga; Lidiman Sahat Martua Sinaga (LINGUISTICA, 2014)
ABSTRACT This descriptive qualitative study is aimed at identifying and describing the types of free collocations found in the articles of Reader’s Digest. By taking a sample of ten articles from different months for each year since 2003 up to 2012, it was found all the four productive free collocations were in the data. Type 4 (Determiner + Adjective + Noun) was the dominant type (53.92 %). This was possible because the adjective in the pattern included the present participle and past participle of verb as adjectives. The other types have the following percentages (in order of the highest level to the lowest level): Type 1 (33.40 %), Type 2 (10.06 %), and Type 3 (2.62 %). The largest number of free collocations was found in the book of Feeding My Fashion (13.48 %). The data analysis also indicates that all the articles contain free collocations. As free collocations are abundant in text, it is suggested that this grammatical construction be introduced as part of strategy to master English.   Keywords: Semantics, Collocations, Reader’s Digest